Dressed for Success? Gendered Appearance Discrimination In the Workplace - Harwood, Catherine (Victoria University of Wellington Law Review, 2007)
Gender is a nebulous concept, linked to one’s self-identity and social acceptance. Gender expression in a heterosexist society is consequently governed by particular social norms and is susceptible to prejudice. It is critical that gender is not a source of permissible discrimination in a central social space, the workplace. Current responses from the law can be ineffective due to the nature of the complaints process and the theory underlying decision-makers’ reasoning. The United States has considerable gender discrimination jurisprudence and is a valuable source of options for law reform. This paper argues that statute and case law in New Zealand should expressly prohibit both inter and intra-gender discrimination. Processes should also be tightened up to avoid claims falling through the cracks in tribunal jurisdictions. Rights are hollow unless they have a real-life impact. While formal recognition does not mean the end to this particularly insidious form of discrimination, it is an important means to shift societal norms. This could generate greater equality in real terms for New Zealanders.